2013
DOI: 10.1617/s11527-013-0096-3
|View full text |Cite
|
Sign up to set email alerts
|

A model combining structure and properties of a 160/220 bituminous binder modified with polymer/clay nanocomposites. A rheological and morphological study

Abstract: The present contribution focuses on the modification of a 160/220 bituminous binder with clay and polymer/clay nanocomposites. Bitumen/polymer/clay ternary blends were prepared using styrene–butadiene–styrene, ethylene vinyl acetate and ethylene methylacrylate copolymers mixed with an organomodified montmorillonite. Dynamic mechanical analyses were performed in the extended domain of stress, temperature and frequency to analyse the thermorheological behaviour of the blends. The time–temperature superposition p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Results of the laboratory modified asphalt binders' characterization can be observed in Table 5. In comparing the results in Table 5 with those provided for the empirical characterization of CAP 50/70 (Table 3) and SBS 60/85 (Table 4), it can be observed that, as expected and also demonstrated by other authors in similar studies [13][14][15][16][17][18][19][20][21], the binders modification caused a penetration decrease and a softening point increase. Notable among these results are the relatively low penetration obtained for the binder 3% NC + 2% SBS and the relatively high softening point for the binder SBS 60/85.…”
Section: Characterization Of Modified Binderssupporting
confidence: 79%
See 2 more Smart Citations
“…Results of the laboratory modified asphalt binders' characterization can be observed in Table 5. In comparing the results in Table 5 with those provided for the empirical characterization of CAP 50/70 (Table 3) and SBS 60/85 (Table 4), it can be observed that, as expected and also demonstrated by other authors in similar studies [13][14][15][16][17][18][19][20][21], the binders modification caused a penetration decrease and a softening point increase. Notable among these results are the relatively low penetration obtained for the binder 3% NC + 2% SBS and the relatively high softening point for the binder SBS 60/85.…”
Section: Characterization Of Modified Binderssupporting
confidence: 79%
“…More recently, the behavior of asphalt binders and mixtures modified with polymers and nanomaterials have been investigated. The results obtained in this line of research have also been positive [13][14][15][16][17][18][19][20][21]. However, most studies have been limited to the binders, and there is a need for more investigations that consider the mixtures, taking into account the interaction between the binder, the granulometry, and the aggregate characteristics.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, storage stability is not simply due to a decrease in density difference between the PRP and ARP phases. Several studies have shown that compatibility between bitumen and polymer also plays a fundamental role [215]. Therefore, the improved storage stability can be ascribed mainly to two factors: decrease in density difference between the PRP and ARP phases and, to a greater extent, to a real bitumen/polymer compatibilizing effect.…”
Section: The Bitumen-polymer-clay Ternary Systemmentioning
confidence: 99%
“…Even though somehow unexpected, this is not surprising, because it was already known that LS might be used as compatibilizer agents in polymer blends. This aspect of LS acting as a polymer/bitumen compatibilizer is fully considered in previous works [83,84] and will not be discussed in detail here. We can limit our work to the observation that the compatibilization is related to selective interactions between clay, polymer, and some bitumen molecules.…”
Section: The Bitumen-polymer-layered Silicate Ternary (Bpls)mentioning
confidence: 99%